2010
DOI: 10.1002/jso.21624
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic features and prognostic factors in alpha‐fetoprotein‐producing gastric cancers: Analysis of 104 cases

Abstract: AFP-positive gastric cancer had more aggressive behavior than that of AFP-negative gastric cancer. In addition to surgery, multimodal therapy should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
146
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(158 citation statements)
references
References 30 publications
(32 reference statements)
10
146
2
Order By: Relevance
“…Four discussion points were evaluated for CEA, CA19-9, and CA72-4 from selected articles as follows: (1) positive rates, (2) clinicopathological significance, (3) prognostic impact, and (4) clinical impact during follow-up after surgery and/or during chemotherapy. Finally, we selected 10 other publications that focused only on AFP [51][52][53][54], CA125 [3,[55][56][57], and STN [58,59] (Fig. 1).…”
Section: Manuscript Selectionmentioning
confidence: 99%
“…Four discussion points were evaluated for CEA, CA19-9, and CA72-4 from selected articles as follows: (1) positive rates, (2) clinicopathological significance, (3) prognostic impact, and (4) clinical impact during follow-up after surgery and/or during chemotherapy. Finally, we selected 10 other publications that focused only on AFP [51][52][53][54], CA125 [3,[55][56][57], and STN [58,59] (Fig. 1).…”
Section: Manuscript Selectionmentioning
confidence: 99%
“…12 Various reports have shown that AFP producing carcinoma of the stomach has a more aggressive behavior than the common gastric cancers in the form of higher incidence of vascular invasion, lymph node and liver metastasis. 13 Data regarding optimum therapy of AFPGC is sparse. The treatment is similar to that of common gastric adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…10 They have high metastatic potential and possibility of vascular invasion, liver and lymph nodal metastases resulting in poor prognosis. 2 In situations where associated liver mass is seen, it may be mistaken for coexistent hepatocellular carcinoma, like the index case.…”
mentioning
confidence: 99%
“…AFP-GC may be divided into two subtypes, consisting of AFP-producing non-hepatoid adenocarcinoma and hepatoid adenocarcinoma. AFP-GC is usually diagnosed in the advanced stages of disease and demonstrates a poor prognosis (20)(21)(22). In patients exhibiting serum AFP levels of >300 ng/ml, the 1-, 3-, and 5-year survival rates are 15.4, 7.7%, and 0%, respectively.…”
Section: Introductionmentioning
confidence: 99%